Sequential treatment in advanced epidermal growth factor receptor-mutated lung adenocarcinoma patients receiving first-line bevacizumab combined with 1st/2nd-generation EGFR-tyrosine kinase inhibitors - Hsu, Ping-Chih; Huang, Chun-Yao; Lin, Yu-Ching; Lee, Suey-Haur; Chiu, Li-Chung; Wu, Chiao-En; Kuo, Scott Chih-Hsi; Ju, Jia-Shiuan; Huang, Allen Chung-Cheng; Ko, Ho-Wen; Wang, Chin-Chou; Yang, Cheng-Ta (Frontiers in Oncology, 2023)
respectively (P = 0.001). The median PFS associated with second-line osimertinib and nonosimertinib therapy was 13.7 and 7.1 months, respectively (hazard ratio (HR) = 0.38; 95% confidence interval (CI), 0.23-0.63; P< 0.001). Patients with a secondary T790M mutation receiving second-line osimertinib treatment had a median overall survival (OS) of 54.3 months, and the median OS was 31.9 months for non-T790M-mutated patients receiving second-line nonosimertinib treatments (HR = 0.36; CI: 0.21-0.62, P < 0.001).The majority of acquired resistance to first-line bevacizumab combined with 1st/2ndgeneration EGFR-TKIs is associated with the T790M mutation. Sequential osimertinib treatment in patients with positive secondary T790M mutation is associated with better outcomes among these patients.